Oleaginous yeast Rhodotorula toruloides biomass effect on the metabolism of Arctic char (Salvelinus alpinus) - Brunel, Mathilde; Burkina, Viktoriia; Pickova, Jana; Sampels, Sabine; Moazzami, Ali A. (Frontiers in Molecular Biosciences, 2022)
Sustainability issues arise when using fish oil and vegetable oils in fish feed production for aquaculture purposes. Microbial production of single cell oil is a potential alternative as a lipid ingredient in the production of fish feed. In this study, we replaced the vegetable oils by the oleaginous yeast Rhodotorula toruloides biomass in the diet of Arctic char (Salvelinus alpinus) and investigated the effects on health and composition. Measurement of fish growth parameters showed a higher liver weight and hepatosomatic index in the experimental group of fish fed partly with yeast biomass compared to a control group fed a diet with vegetable oils. No significant differences in the lipid content of muscle and liver tissues were found. The fatty acid profiles in the muscle of both fish groups were similar while the experimental fish group had a higher amount of monounsaturated fatty acids in the liver. Histology of livers showed no significant difference in the number lipid droplets. Size of hepatic lipid droplets seemed to be related to liver fat content. Quantification of metabolites in the liver revealed no differences between the fish groups while plasma metabolites involved in energy pathways such as alanine 3-hydroxybutyrate, creatinine, serine, betaine and choline were significantly higher in the experimental fish group.